REPRESENTASI PERSAHABATAN DALAM FILM AGAK LAEN - Felita Irham Rachman; Muhammad Bayu Widagdo (Interaksi Online, 2026)
Film Agak Laen (2024) emerged as one of the most phenomenal Indonesian films, attracting over 9 million viewers. Beyond its horror-comedy appeal, the film constructs a deep representation of friendship through the characters of Bene, Boris, Oki, and Jegel who navigate urban economic pressures. This study aims to analyze how the reality of friendship is represented in the film Agak Laen, and to uncover the denotative, connotative, and mythological meanings hidden behind those representations. Using a qualitative approach with a critical paradigm, this research applies Roland Barthes' semiotic analysis to examine 17 selected lexia comprising visual signs, dialogue, and symbolic elements. The analysis uses both syntagmatic and paradigmatic methods, specifically Barthes' five reading codes (hermeneutic, proairetic, symbolic, cultural, and semic). The findings reveal that friendship among the four main characters is constructed as a profound moral commitment that transcends formal social relations. At the denotative level, the film records physical actions, panic, and cooperation among characters in managing a haunted house business and concealing a visitor's death. At the connotative level, these absurd actions signify loyalty, group solidarity, moral support, and psychological defense mechanisms using humor to ease fear amid economic crisis. At the mythological level, the film naturalizes the idea that unconditional loyalty and collective cooperation (gotong royong) are the ideal moral standards for lower-class Indonesian society facing systemic inequality. The film also implicitly critiques modern society's culture of sensation that commodifies fear and tragedy for economic virality.